Strength degradation of soft interlayer under dry-wet cycles based on 3D printing technology - Hao LIU; Wen ZHANG; Lei LU (Shuiwen dizhi gongcheng dizhi)
Soft interlayers are critical geological formations that significantly impact the stability of slopes in water and hydropower engineering projects. This study investigated the shear mechanical characteristics and failure mechanism of the soft interlayer under dry-wet cycle conditions with a focus on the left bank shoulder slope of the Caizi Dam pumped storage power station’s lower reservoir. Real rock morphology characteristics were replicated using 3D printing technology to create structural surfaces, and the roughness coefficient JRC of different structural surfaces was then calculated. Subsequently, shear tests were conducted on soft interlayers containing artificial joint surfaces subjected to dry-wet cycles. The results indicate that, after multiple dry-wet cycles, the shear strength decreases exponentially as the number of cycles increases, and eventually approaches a very low stable value, which is approximately 5% of the initial strength. Moreover, the shear strength is positively correlated with the roughness of the structural plane. The shear stress-strain curve of the soft interlayer exhibits a stepwise decrease during the failure stage, with the magnitude of this decrease in the residual curve proportional to structural surface roughness. Samples with higher roughness on the structural surface reach the residual strength stage at a shorter shear displacement, and the residual strength decreases as the number of dry-wet cycles increases. This study provides valuable insights for slope stability assessments in energy dissipation and water storage projects.